2011
DOI: 10.1111/j.1440-1797.2011.01495.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes of renal vitamin D metabolic enzyme expression and calcium transporter abundance in obstructive nephropathy

Abstract: The effects of urinary-tract obstruction on renal function have been clarified. However, there is little known about the change of renal vitamin D metabolic enzyme expression and vitamin D-dependent calcium transporting proteins expression in obstructive nephropathy. The male mice were subjected to unilateral ureteral obstruction (n = 10) or sham operation (n = 10). All mice were killed on day 7 after the surgical operation. Kidney sections were stained with Masson's trichrome and gene expression was analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The value of serum calcium in UUO mice was 2.02 mmol/L, which is below the lower limit of the normal range (2.07 mmol/L). Our recent kidney obstruction study using UUO mice demonstrated the altered renal vitamin D metabolism and a reduction of calcium transporter abundance 23 . Similar causes may account for the reduced level of serum calcium of UUO mice in this study.…”
Section: Discussionsupporting
confidence: 75%
“…The value of serum calcium in UUO mice was 2.02 mmol/L, which is below the lower limit of the normal range (2.07 mmol/L). Our recent kidney obstruction study using UUO mice demonstrated the altered renal vitamin D metabolism and a reduction of calcium transporter abundance 23 . Similar causes may account for the reduced level of serum calcium of UUO mice in this study.…”
Section: Discussionsupporting
confidence: 75%
“…The mouse with unilateral ureteral obstruction (UUO) is a well-established model of tubulointerstitial fibrosis of the kidney as the interstitial fibrosis is a hallmark of chronic renal failure [60]. We previously reported the vitamin D signaling attenuates renal fibrosis in obstructive nephropathy by suppressing the renin-angiotensin system (RAS) [61], furthermore, we found the mice developed hypocalcaemia and hyperparathyroidism after 7 days of ureteric obstruction [62], and the down-regulation of Cbfa1 and Col mRNA expression ( Fig.…”
Section: Obstructive Nephropathymentioning
confidence: 99%
“…3 We previously reported changes in the renal expression of vitamin D metabolic enzymes and changes in calcium transporter abundance following obstructive nephropathy in mice subjected to UUO 4 and demonstrated early molecular responses of bone to unilateral obstructive nephropathy in the UUO model. 5 However, associated with the pathological alterations of vitamin D metabolism and the expression of genes involved in bone metabolism, whether trabecular bone microstructure would deteriorate in UUO mice remained to be clarified.…”
Section: Introductionmentioning
confidence: 96%